A reduced order mathematical model of the blast furnace raceway with and without pulverized coal injection for real time plant application. (2nd October 2018) - Sau, D. C.; Das, S. K.; Mandal, G. K.; Bandyopadhyay, D.
Abstract: Pulverized coal is injected into blast furnace tuyeres to reduce coke consumption as well as to reduce hot metal production cost. Knowledge of the combustion behavior of pulverized coal in the blast furnace raceway zone and accumulation of unburnt char are of paramount importance. To alleviate the problem of high computational time of a multidimensional model, a reduced order raceway model of the blast furnace has been proposed for real time plant application. The model is capable of predicting radial temperature and gas composition profiles in the raceway zone with and without pulverized coal injection (PCI). Influence of all the key operating process parameters such as PCI rate, blast temperature, blast volume, oxygen enrichment and steam addition on the raceway combustion behavior, temperature and gas composition profiles as well as raceway depth have been investigated and validated with literature and plant database, wherever possible. It has been observed that with increasing PCI rate on a fixed fuel rate basis, the peak gas temperature (PGT) decreases and the location of PGT tends to shift toward tuyere nose. The present model is an efficient computational tool to predict the raceway process variables for online application, in synchronization with plant operation.